Careless Talk Costs Lives: The Causes and Effects of Marginalising Peacebuilding Practitioners with Caring Responsibilities. Issue 4 (8th August 2022) - Gordon, Eleanor
ABSTRACT : This article examines the departure and broader marginalisation of staff with parental and other caring responsibilities from peacebuilding organisations. By drawing from the results of a global survey with peacebuilding practitioners, this research highlights the practical, organisational, cultural, and normative challenges that cause this marginalisation and the resultant individual, organisational, and sectoral harms. The article argues that the resultant harms are highly gendered and extend beyond the individual peacebuilder to the peacebuilding work being undertaken and the type of peace being built. This demands an ethics of care in peacebuilding is advanced, and peacebuilding organisations direct the 'care lens' inwards.